2005
DOI: 10.1111/j.0022-1112.2005.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic isolation between Atlantic and Mediterranean albacore populations inferred from mitochondrial and nuclear DNA markers

Abstract: Genetic population structure of Atlantic and Mediterranean albacore Thunnus alalunga was investigated using nucleotide sequence variations of the glucose-6-phosphate dehydrogenase gene intron (G6PD) and the mitochondrial DNA (mtDNA) D-loop region (Dloop). Restriction analysis using Ase I digestion detected two major restriction types (A and B) at the Dloop locus with strong frequency differences between Atlantic and Mediterranean samples. Thirty-six individuals of 100 Mediterranean albacore were of the B type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
2
18
1
1
Order By: Relevance
“…While initial studies did not find differences, probably due to the small sample size used by Viñas et al (1999) or the lack of resolution of allozyme markers in the study by Pujolar et al (2003), genetic differences were detected using other types of genetic markers such as blood groups (Arrizabalaga et al 2004) and mtDNA (Viñas et al 2004, Nakadate et al 2005. In the present study, Mediterranean samples showed the highest and most significant F ST values when compared to the oceanic ones (pairwise comparisons).…”
Section: Genetic Diversity Between Populationscontrasting
confidence: 56%
See 1 more Smart Citation
“…While initial studies did not find differences, probably due to the small sample size used by Viñas et al (1999) or the lack of resolution of allozyme markers in the study by Pujolar et al (2003), genetic differences were detected using other types of genetic markers such as blood groups (Arrizabalaga et al 2004) and mtDNA (Viñas et al 2004, Nakadate et al 2005. In the present study, Mediterranean samples showed the highest and most significant F ST values when compared to the oceanic ones (pairwise comparisons).…”
Section: Genetic Diversity Between Populationscontrasting
confidence: 56%
“…Additionally, based on 12 micro sa tel lite loci, Davies et al (2011) described genetic differentiation within the Me diterranean Sea and between North Atlantic and South Pacific samples. Previous studies on the genetic structure of albacore populations used other types of markers, such as allozymes (Pujolar et al 2003), mtDNA (Chow & Ushiama 1995, Yeh et al 1997, Viñas et al 1999, Nakadate et al 2005, Wu et al 2009, and blood groups (Arriza balaga et al 2004). Taken to gether, these stu dies showed genetic differences be tween the North Pacific and Indian Oceans, but barely de tected, heterogeneity within oceans (Chow & Ushi ama 1995, Nakadate et al 2005, or even between North Atlantic and Mediterranean stocks (Viñas et al 1999, Pujolar et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a variety of molecular markers, including mtDNA and nDNA, provided very similar patterns of population structure for other pelagic species exhibiting similar distribution as dolphinfish. This is the case of the swordfish X. gladius (Alvarado-Bremer et al, 2005b), the albacore T. alalunga (Nakadate et al, 2005) and other small pelagic species, such as the Atlantic bonito Sarda sarda (Viñas et al, 2004b). These studies reported highly significant differences between the Northeastern Atlantic and Mediterranean populations due to the following: (a) the combined effects of vicariance followed by a secondary contact, (b) differences in the historical demography, or (c) isolation by distance.…”
Section: Mediterranean Isolationmentioning
confidence: 99%
“…Despite some evidence of migrations between the Atlantic and the Mediterranean , the Mediterranean albacore populations constitute a genetically differentiated stock (LopezRodas et al, 2002;Viñas et al, 2004;Nakadate et al, 2005) that up until now have not been as intensively exploited as Atlantic stocks. Reported landings in past decades have usually fluctuated between 2000 and 4000 tons, with a maximum of 4866 tons in 2001 (Anon., 2004), most of them captured by Italian and Greek fleets.…”
Section: Diet Of Larval Albacore Thunnus Alalunga (Bonnaterre 1788) mentioning
confidence: 99%